A comparison of climate change impacts on park values on four Queensland World Heritage National Parks in Australia. Issue 3 (3rd July 2018) - Tanner-McAllister, Sherri L.; Rhodes, Jonathan R.; Hockings, Marc
ABSTRACT: Protected areas will vary in how they respond to climate-related threats and impacts. An important step in adapting protected area management to respond to climate change is identifying how protected areas and their values may be impacted. This requires an understanding of the ecological and social system impacting on the particular values so that consideration of management options and issues can be informed by this understanding. A set of Bayesian belief networks were developed to assess impacts and management issues for three key values (stream-dwelling frogs, cool temperate forest and recreational walking access) across four National Parks (Springbrook, Lamington, Mount Barney and Main Range) in Queensland, Australia. The aim was to assess how those values may be impacted by climate change, how the parks differ in relation to likely impact and options for management adaptation. We observed, depending on a protected area's physical and socio-ecological characteristics, that the values were likely to be differently affected across the parks and management responses will need to take account of these differences.